2019
DOI: 10.1177/2325967119847978
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Lower Limb Tightness and Practice Time Among Adolescent Baseball Players With Symptomatic Osgood-Schlatter Disease

Abstract: Background: Osgood-Schlatter disease (OSD) is characterized by traction apophysitis of the tibial tuberosity. Few studies on symptomatic and asymptomatic OSD have correlated findings with clinical examination. Purpose: To investigate the relationship between lower limb tightness and practice time among adolescent baseball players with symptomatic OSD. Study Design: Cross-sectional study; Level of evidence, 3. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 24 publications
1
31
1
Order By: Relevance
“…A cross-sectional study compared lower limb tightness in adolescents with and without OSD and revealed that HBD was signi cantly higher in those with OSD. However, this study found no differences in SLRA (12). Our study showed that there was no obvious association between the new onset of AKP and HBD.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…A cross-sectional study compared lower limb tightness in adolescents with and without OSD and revealed that HBD was signi cantly higher in those with OSD. However, this study found no differences in SLRA (12). Our study showed that there was no obvious association between the new onset of AKP and HBD.…”
Section: Discussioncontrasting
confidence: 80%
“…There have been several studies on the risk factors for AKP in children and adolescents. Some researchers have reported that quadriceps tightness is associated with AKP (11) (12). A cross-sectional study compared lower limb tightness in adolescents with and without OSD and revealed that HBD was signi cantly higher in those with OSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies reported on tibial tuberosity maturation 16,18,19,22,23,28,42‐45 and six of these did not include controls 18,19,22,42‐44 . Most studies (n = 6) used the Ehrenborg classification or a modified version ranging from the cartilaginous stage to a bony/mature attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Omodaka et al [ 17 ] demonstrated a significant relationship between the duration of training and the onset of OSD. Hall et al [ 18 ] revealed a fourfold increase in the risk of OSD when sport-specific training is performed during adolescence.…”
Section: Discussionmentioning
confidence: 99%